URBAN EXPERIENCE AND DESIGN : Contemporary Perspectives on Improving the Public Realm - Hollander, Justin B., editor 591709; Sussman, Ann, editor 591707; Taylor FrancisLink (Online service) 632098 (New York, NY : Routledge/Taylor & Francis Group, 2020)
Embracing a biological and evolutionary perspective to explain the human experience of place, Urban Experience and Design explores how cognitive science and biometric tools provide an evidence-based foundation for architecture and planning. Aiming to promote the creation of a healthier and happier public realm, this book describes how unconscious responses to stimuli, outside our conscious awareness, direct our experience of the built environment and govern human behavior in our surroundings. This collection contains 15 chapters, including contributions from researchers in the US, the UK, the Netherlands, France and Iran. Addressing topics such as the impact of eye-tracking analysis and seeing beauty and empathy within buildings, Urban Experience and Design encourages us to reframe our understanding of design, including the narrative of how modern architecture and planning came to be in the first place. This volume invites students, academics and scholars to see how cognitive science and biometric findings give us remarkable 21st-century metrics for evaluating and improving designs, even before they are built.